2022
DOI: 10.1002/mrc.5256
|View full text |Cite
|
Sign up to set email alerts
|

Computational NMR of natural products: On the way to super large molecules exemplified with alasmontamine A

Abstract: H and 13 C nuclear magnetic resonance (NMR) chemical shifts of a tetrakis monoterpene indole alkaloid alasmontamine A with a molecular formula of C 84 H 91 N 8 O 12 have been calculated at the PBE0/pcSseg-2//pcseg-2 level of theory on M06-2X/aug-cc-pVDZ geometry. In the course of the preliminary conformational search, six true minimum energy conformers were identified that can contribute to the actual conformation of this huge alkaloid. Calculated chemical shifts generally demonstrated a good agreement with av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Quantum chemical calculations of NMR parameters have also been extensively used for the precise determination of diastereomerism of natural products with multiple asymmetric centers [ 138 , 141 , 142 , 143 , 158 , 159 , 160 , 161 ]. On the contrary, in the field of lipid hydroperoxides, only three papers have so far been reported [ 138 , 141 , 156 ].…”
Section: Structural Investigations Based On Quantum Chemical Calculat...mentioning
confidence: 99%
“…Quantum chemical calculations of NMR parameters have also been extensively used for the precise determination of diastereomerism of natural products with multiple asymmetric centers [ 138 , 141 , 142 , 143 , 158 , 159 , 160 , 161 ]. On the contrary, in the field of lipid hydroperoxides, only three papers have so far been reported [ 138 , 141 , 156 ].…”
Section: Structural Investigations Based On Quantum Chemical Calculat...mentioning
confidence: 99%
“…The equilibrium structure of alasmontamine A was later optimized at the M06-2X/aug-cc-pVDZ level (diffused functions were used only on N and O atoms possessing multiple lone pairs), while calculation of 1 H and 13 C NMR chemical shifts was carried out using the PBE0 functional with the pcSseg-2 basis set for H and C atoms and pcseg-2 on N and O atoms. [361] It was found that calculated 1 H and 13 C NMR chemical shifts provided good correlation with their experimental values, as illustrated in Figure 35. The only marked deviation between calculated and experimental 13 C NMR chemical shifts were reported for C-3 00 and C-23 000 which possibly points to the need for their reassignment.…”
Section: Natural Productsmentioning
confidence: 62%
“…For the sake of better visualability, hydrogen atoms are not shown in the molecular structure; for details, see paper by Semenov and Krivdin. [361] 79…”
Section: Natural Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2D chemical structure of this large alkaloid providing the enumeration of atoms (with omitting hydrogens for clarity) is provided below, while its 3D structure is presented in Figure 1 . A preliminary communication dealing with the conformational study of this compound was published in Magnetic Resonance in Chemistry [ 10 ].…”
Section: Introductionmentioning
confidence: 99%